All-solid-state metal lithium battery interface layer material and preparation method thereof
By using radio frequency magnetron sputtering method to deposit carbon composite film materials in all-solid metal lithium batteries, forming an interface layer, the interface problem between metal lithium and solid electrolyte is solved, better lithium ion conduction and battery stability are achieved, and the cycle life of the battery is extended.
Patent Information
- Application Number
- CN202411754852.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-11
AI Technical Summary
In all-solid metal lithium batteries, the interface problems between metal lithium and solid electrolytes lead to uneven conduction of lithium ions, local current enrichment, increased interface impedance, unstable Li dendrite growth and electrochemical mechanical degradation, limiting the performance and life of the battery.
The carbon composite film material with mixed electron ion conductive phases is deposited at low temperature on the surface of the solid electrolyte by radio frequency magnetron sputtering to form an interface layer, improve the interface contact between metal lithium and solid electrolyte, fix the deposition site of lithium, and reduce the generation of lithium dendrites.
It effectively reduces the interface impedance, improves the uniform conduction of lithium ions, extends the cycle life of the battery, and improves the stability and energy density of the battery.
Smart Images

Figure CN119601801A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to an all-solid-state metal lithium battery interface layer material and a preparation method thereof. Background Art
[0002] All-solid-state batteries use solid electrolytes instead of traditional liquid electrolytes, eliminating the risk of liquid electrolytes being easily leaked and flammable and explosive, effectively improving the safety of the battery. The wide voltage range of solid electrolytes also allows the use of negative electrode materials with higher energy density, such as metallic lithium, thereby greatly improving the energy density and endurance of all-solid-state batteries. In addition, all-solid-state batteries have a wider operating temperature range and longer cycle life. Their volume energy density, which is much higher than that of traditional liquid batteries, makes the batteries thinner and lighter, and suitable for a variety of application scenarios such as portable devices and electric vehicles. Lithium metal is chosen as the negative electrode because lithium has an extremely high theoretical specific capacity (3860mAh g -1 ) and extremely low electrode potential (about -3.04V vs standard hydrogen electrode), it is an ideal choice for the next generation of high energy density all-solid-state batteries. These advantages make all-solid-state metal lithium batteries a strong candidate for the new era of energy storage technology.
[0003] The electrode / electrolyte interface plays an important role in determining the performance of all-solid-state metal lithium batteries. Due to the complex electrochemical reactions, charge transfer and mass transfer occurring at the interface during the charge and discharge process, they exhibit complex dynamic characteristics. The dynamic changes of the metal lithium negative terminal interface are easier to detect and improve than the positive terminal, which has attracted widespread attention in the academic community. At the metal lithium / solid electrolyte interface of all-solid-state metal lithium batteries, unstable Li dendrite growth, undesirable interfacial reactions and electrochemical mechanical degradation are the main problems that limit battery performance.
[0004] First, the solid electrolyte lacks fluidity, so it has poor wettability with metallic lithium, and the solid-solid contact area is small and uneven, which will lead to uneven conduction of lithium ions and local current enrichment, and the interface impedance will increase accordingly. Secondly, metallic lithium has strong reducing properties and is prone to side reactions with solid electrolytes, resulting in poor interface stability. In addition, metallic lithium has poor chemical stability, and uneven deposition and stripping will occur during the cycle, and large volume changes will occur. The effective area of contact between metallic lithium and solid electrolyte is further reduced, which is not conducive to the performance of all-solid-state batteries. In summary, the interface problem between metallic lithium and solid electrolytes has become a bottleneck restricting the development of all-solid-state metal lithium batteries, so the introduction of an interface layer is very necessary.
[0005] There are many existing studies on the interface layer of all-solid-state batteries, such as oxides, carbides, sulfides, etc. However, they are all added single electron conductors or ion conductors, and often use complex process steps, high preparation temperatures, long processing times, or wet chemical methods to form an uneven interface layer with poor mechanical stability. The all-solid-state metal lithium battery interface layer material and preparation method of the present invention overcome the above shortcomings. The carbon composite film material obtained by magnetron sputtering not only has a certain elasticity, but also has improved mechanical stability. By doping with nitrogen elements or sticking metal sheets on graphite targets to dope metal elements, mixed conductors of electrons and ions are obtained. Compared with all-solid-state metal lithium batteries with unmodified interface layers, the cycle life and stability are effectively improved. Summary of the invention
[0006] The purpose of the present invention is to overcome the deficiencies of the prior art, provide an all-solid-state metal lithium battery interface layer material and a preparation method thereof, adopt a radio frequency magnetron sputtering method, deposit a carbon composite film material on the surface of a solid electrolyte under low temperature conditions, the preparation method is simple in process, short in time, and does not require additional treatment, and the obtained carbon composite film interface layer with a mixed electronic ion conductive phase can effectively improve the interface contact between the solid electrolyte and the metal lithium negative electrode, fix the deposition site of the metal lithium, reduce the enrichment of the local current, thereby reducing the generation of lithium dendrites, and is beneficial to the lithium reaction kinetics, and also has a certain mechanical elasticity of stress and strain resistance, alleviates the huge volume change of the lithium metal negative electrode during the cycle, and reduces the generation of lithium pores. Compared with unmodified all-solid-state metal lithium batteries, the cycle life and stability can be effectively improved.
[0007] The first aspect of the present invention relates to an all-solid-state metal lithium battery interface layer material, which is located between a solid electrolyte and a metal lithium negative electrode and is composed of a carbon composite film material with a mixed electronic ion conductive phase.
[0008] The second aspect of the present invention relates to a method for preparing the aforementioned all-solid-state metal lithium battery interface layer material, comprising the following steps:
[0009] Step S1: using a radio frequency magnetron sputtering process, installing a target material and a prepared solid electrolyte sample after surface cleaning, adjusting the target-substrate distance, closing the coating chamber, and evacuating it;
[0010] Step S2: introducing working gas such as pure nitrogen, pure argon or nitrogen-argon mixed gas into the vacuum chamber, controlling the gas flow rate and ratio of the working gas, setting parameters such as gas pressure, sputtering power, substrate temperature and sputtering time during sputtering, and obtaining a carbon composite thin film material, i.e., the all-solid-state metal lithium battery interface layer, after sputtering is completed.
[0011] In an optional embodiment, the thickness of the interface layer is 5 nm to 5 μm, and the corresponding positive electrode thickness is at least 10 times or more of the thickness of the interface layer.
[0012] In an optional embodiment, the target material is a high-purity commercial graphite target, and the metal sheet is cut into 10-50 mm 2 2 to 10 pieces of patches are attached in pairs to the symmetrical sputtering ring position of the target. The thickness of the metal sheet should be uniform and can be flexibly adjusted according to the needs of sputtering time. The metal can be selected from one or more of Au, Ag, Cu, Al, Mg, Zn, Ti, In, etc.
[0013] In an alternative embodiment, the substrate temperature is 15-200°C.
[0014] In an optional embodiment, the coating chamber is evacuated to a pressure of ≤1×10 -4 Pa, the working gas is pure nitrogen, pure argon or a mixture of nitrogen and argon.
[0015] In an optional embodiment, when the working gas is nitrogen, the nitrogen flow rate is 5 to 100 sccm; when the working gas is argon, the argon flow rate is 5 to 100 sccm; when the working gas is a mixture of nitrogen and argon, the nitrogen flow rate is 5 to 100 sccm, and the argon flow rate is 0 to 100 sccm.
[0016] In an optional embodiment, the RF sputtering power is 40 to 200 W, and the sputtering time is 60 s to 5 h.
[0017] 1. In an optional embodiment, the solid electrolyte type includes one or more of an amorphous electrolyte (LiPON, etc.), a perovskite type, a NASICON type, a garnet type, a halide type, a sulfide type, and a polymer / inorganic composite electrolyte type, and the selected positive electrode material may include all all-solid-state battery positive electrode materials.
[0018] Compared with the prior art, the present invention has the following significant beneficial effects:
[0019] 1. The interface layer material of the all-solid-state metal lithium battery of the present invention is composed of a carbon composite thin film material with a mixed electronic ion conductive phase. The interface layer is located between the solid electrolyte and the metal lithium, which can effectively improve the interface contact between the solid electrolyte and the metal lithium negative electrode, reduce the interface impedance, facilitate lithium ion transport, and facilitate lithium reaction kinetics. Compared with the unmodified all-solid-state metal lithium battery, it can effectively improve the interface stability and have a longer cycle life.
[0020] 2. The preparation method of the present invention adopts a radio frequency magnetron sputtering method to deposit a carbon composite thin film material on the surface of a solid electrolyte under low temperature (≤200°C) conditions. Compared with other preparation methods, the process is simple, time-saving, and does not require additional treatment. The obtained interface layer is tightly combined with the solid electrolyte and metallic lithium, which effectively improves the interface contact and enhances the interface stability. It effectively solves the negative electrode / electrolyte interface problem caused by the large volume change of the metallic lithium negative electrode during the cycle, and has broad prospects for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is the abstract accompanying drawing of the present invention.
[0022] Figure 2 It is a SEM cross section and corresponding element mapping diagram of the nitrogen-doped carbon composite film interface layer modified on the solid electrolyte obtained in Example 1 of the present invention.
[0023] Figure 3 This is a cycle performance diagram of the all-solid-state metal lithium battery with a nitrogen-doped carbon composite film interface layer obtained in Example 1 of the present invention.
[0024] Figure 4 This is a cycle performance diagram of the unmodified all-solid-state metal lithium battery obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0025] In order to better understand the technical content of the present invention, specific embodiments are given and described as follows in conjunction with the accompanying drawings.
[0026] Various aspects of the present invention are described in this disclosure with reference to the accompanying drawings, in which many illustrative embodiments are shown. The embodiments of the present disclosure are not necessarily defined to include all aspects of the present invention. It should be understood that the various concepts and embodiments introduced above, as well as those described in more detail below, can be implemented in any of many ways.
[0027] The invention provides an all-solid-state metal lithium battery interface layer material, which is deposited on the surface of a solid electrolyte for a period of time to obtain a carbon composite film material with a mixed electronic ion conductive phase.
[0028] In an optional embodiment, the thickness of the interface layer film is 5 nm to 5 μm.
[0029] The present invention also provides a method for preparing an interface layer material of an all-solid-state metal lithium battery, which adopts a radio frequency magnetron sputtering method to directly deposit a carbon composite thin film material on the surface of a solid electrolyte at a low temperature (≤200°C). The preparation method has a simple process, short time consumption, good repeatability, and no need for additional treatment. The obtained interface layer material is uniform and dense, which effectively improves the interface contact between the solid electrolyte and metal lithium, and effectively solves the interface problem between the metal lithium negative electrode and the solid electrolyte caused by the large volume change of metal lithium during the cycle, reduces the interface impedance, and exhibits more stable cycle performance compared to unmodified all-solid-state metal lithium batteries.
[0030] In another exemplary embodiment of the present invention, a method for preparing the aforementioned carbon composite thin film material is provided, comprising the following steps:
[0031] The radio frequency magnetron sputtering process is adopted, and a high-purity commercial graphite target is used as the target material. After the target material and the substrate are installed, the target-substrate distance is adjusted, the coating chamber is closed and evacuated, and the working gas is introduced. After setting the sputtering power, substrate temperature and sputtering time, sputtering is started, and the required all-solid-state metal lithium battery interface layer material is deposited on the surface of the solid electrolyte;
[0032] In an alternative embodiment, the substrate temperature is 15-200°C.
[0033] In an optional embodiment, the coating chamber is evacuated to a pressure of ≤1×10 -4 Pa, the working gas is pure nitrogen, pure argon or a mixture of nitrogen and argon.
[0034] In an optional embodiment, when the working gas is nitrogen, the nitrogen flow rate is 5 to 100 sccm; when the working gas is argon, the argon flow rate is 5 to 100 sccm; when the working gas is a mixture of nitrogen and argon, the nitrogen flow rate is 5 to 100 sccm, and the argon flow rate is 0 to 100 sccm.
[0035] In an optional embodiment, the RF sputtering power is 40 to 200 W, and the sputtering time is 60 s to 5 h.
[0036] In an optional embodiment, the solid electrolyte type includes one or more of an amorphous electrolyte (LiPON, etc.), a perovskite type, a NASICON type, a garnet type, a halide type, and a sulfide type.
[0037] The following will combine specific embodiments and comparative examples, as well as their testing processes, to more clearly describe the exemplary implementation of various aspects of the present invention.
[0038] [Example 1]
[0039] preparation
[0040] Select 1μm thick LiCoO 2 As the positive electrode, LiPON as the solid electrolyte, using high-purity commercial graphite target material, after installing the target material and substrate, the target-substrate distance was adjusted to 10 cm, and the coating chamber was evacuated to 1.0×10 -4 Below Pa, 60sccm of nitrogen is introduced as the working gas; the sputtering power is set to 80W, the substrate temperature is 25°C, and the sputtering time is 600s. It is known that the thickness of the film grown for 2h is about 600nm, and the growth rate is about 5nm / min. The thickness of the carbon composite film actually sputtered in this embodiment is about 50nm. Therefore, a nitrogen-doped carbon composite film with a thickness of 50nm can be directly obtained on the surface of LiPON.
[0041] SEM
[0042] Figure 1 It is the SEM surface, cross section and corresponding carbon-nitrogen element mapping diagram of the nitrogen-doped carbon composite film obtained in Example 1. It can be seen from the figure that the film surface is dense and smooth, and the carbon and nitrogen elements are evenly distributed in the interface layer of the carbon composite film.
[0043] Electrochemical performance test
[0044] The electrochemical test method of the nitrogen-doped carbon composite film interface layer obtained in Example 1 is:
[0045] The nitrogen-doped carbon composite film is located between the LiPON solid electrolyte and the metal lithium anode. The prepared all-solid-state metal lithium battery is as follows from bottom to top: substrate-Pt / Ti-LiCoO 2 -LiPON-C / N-Li, and conduct electrochemical performance tests on the prepared all-solid-state metal lithium battery.
[0046] Figure 2 is 0.5A g -1 From the electrochemical performance test graph obtained in the voltage range of 3 to 4.5 V under current density, it can be seen that the capacity retention rate of the all-solid-state metal lithium battery is still 85.3% after 200 cycles.
[0047] [Example 2]
[0048] Use 1μm thick LiCoO 2 As the positive electrode, LiPON as the solid electrolyte, high-purity commercial graphite target material was used. After the target material was installed, the target-substrate distance was adjusted to 10 cm, and the coating chamber was evacuated to 1.0×10 -4Below Pa, 80sccm of nitrogen is introduced as the working gas; the sputtering power is set to 80W, the substrate temperature is 25°C, and the sputtering time is 600s. It is known that the thickness of the film grown for 2h is about 640nm, and the growth rate is about 5.33nm / min. The actual thickness of the carbon-nitrogen film obtained by sputtering in this embodiment is about 55nm. Therefore, a nitrogen-doped carbon composite film interface layer with a thickness of 55nm is obtained on the surface of LiPON.
[0049] The nitrogen-doped carbon composite film is located between LiPON and the metal lithium anode. The prepared all-solid-state metal lithium battery is as follows from bottom to top: substrate-Pt / Ti-LiCoO 2 -LiPON-C / N-Li, the electrochemical performance of the prepared all-solid-state metal lithium battery was tested. -1 Under the current density, the capacity retention rate of the all-solid-state metal lithium battery is still 80.0% after 200 cycles in the 3-4.5V voltage range.
[0050] [Example 3]
[0051] Use 1μm thick LiCoO 2 As the positive electrode, LiPON as the solid electrolyte, high-purity commercial graphite target material was used. After the target material was installed, the target-substrate distance was adjusted to 10 cm, and the coating chamber was evacuated to 1.0×10 -4 Below Pa, 40sccm of nitrogen is introduced as the working gas; the sputtering power is set to 60W, the substrate temperature is 25°C, and the sputtering time is 600s. It is known that the thickness of the film grown for 2h is about 540nm, and the growth rate is about 4.5nm / min. The actual thickness of the carbon composite film obtained by sputtering in this embodiment is about 45nm, so a nitrogen-doped carbon composite film interface layer with a thickness of 45nm is obtained on the LiPON surface.
[0052] The nitrogen-doped carbon composite film is located between LiPON and the metal lithium anode. The prepared all-solid-state metal lithium battery is as follows from bottom to top: substrate-Pt / Ti-LiCoO 2 -LiPON-C / N-Li, the electrochemical performance of the prepared all-solid-state metal lithium battery was tested. -1 The current density is 3-4.5V. After 200 cycles in the voltage range, the capacity retention rate of the all-solid-state battery is still 81.7%.
[0053] [Example 4]
[0054] Use 30μm thick LiCoO 2 As the positive electrode, LiPON is used as the solid electrolyte, and a high-purity commercial graphite target is used. The surface is symmetrically attached with a 5mm square and an area of 25mm 2After the target material is installed, the target-substrate distance is adjusted to 10 cm, and the coating chamber is evacuated to 1.0×10 -4 Below Pa, 60sccm of argon is introduced as the working gas; the sputtering power is set to 80W, the substrate temperature is 25°C, and the sputtering time is 3h. It is known that the thickness of the film grown for 5h is about 240nm, and the growth rate is about 48nm / h. The actual thickness of the carbon composite film obtained by sputtering in this embodiment is about 160nm, so an aluminum-doped carbon composite film interface layer with a thickness of 160nm is obtained on the LiPON surface.
[0055] The aluminum-doped carbon composite film is located between LiPON and the metallic lithium anode. The prepared all-solid-state battery is from bottom to top: substrate-Pt / Ti-LiCoO 2 -LiPON-C / Al-Li, the electrochemical performance of the prepared all-solid-state battery was tested. -2 The current density is 3-4.2V. After 250 cycles in the voltage range, the capacity retention rate of the all-solid-state metal lithium battery is still 71.39%.
[0056] [Comparative Example 1]
[0057] The original all-solid-state metal lithium battery without interface modification was prepared by using 1 μm thick LiCoO 2 Using LiPON as the positive electrode and LiPON as the solid electrolyte, the metallic lithium negative electrode was directly evaporated on the surface of LiPON, and the electrochemical performance of the obtained all-solid-state metal lithium battery was tested.
[0058] Figure 3 is 0.5A g -1 The electrochemical performance test graph obtained in the current density and voltage range of 3-4.5V shows that the capacity retention rate of the all-solid-state battery is only 57.0% after 200 cycles.
[0059] [Comparative Example 2]
[0060] The original all-solid-state metal lithium battery without interface modification was prepared by using 30 μm thick LiCoO 2 Using LiPON as the positive electrode and LiPON as the solid electrolyte, the metallic lithium negative electrode was directly evaporated on the surface of LiPON, and the electrochemical performance of the obtained all-solid-state metal lithium battery was tested.
[0061] At 0.2 mA cm -2 The current density is 3-4.2V. After 50 cycles in the voltage range, the capacity retention rate of the all-solid-state metal lithium battery is still 50.8%.
[0062] Although the present invention is disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.
Claims
1. An all-solid-state metal lithium battery interface modification layer material, characterized in that: Located between the same electrolyte and the metallic lithium negative electrode, it is a composite layer thin film material composed of carbon composite / nitrogen-doped carbon and metal. The preparation method of the all-solid-state metal lithium battery interface modification layer material is: Step S1: using a radio frequency magnetron sputtering process, after the target material and the prepared homogeneous electrolyte sample are installed and the surface is cleaned, the target-substrate distance is adjusted, the coating chamber is closed, and it is evacuated; Step S2: introducing working gas such as pure nitrogen, pure argon or a mixture of nitrogen and argon into the vacuum chamber, controlling the gas flow rate and ratio of the working gas, setting parameters such as gas pressure, sputtering power, substrate temperature and sputtering time during sputtering, and obtaining a carbon composite thin film material, i.e., the interface modification layer of the all-solid-state metal lithium battery, after sputtering is completed.
2. The all-solid-state metal lithium battery interface modification layer material according to claim 1, characterized in that: The thickness of the carbon composite film material is 5 nm to 5 μm, and the corresponding positive electrode thickness should be 10 times or more of the thickness of the interface layer.
3. The method for preparing the interface modification layer material of the all-solid-state metal lithium battery according to claim 1, characterized in that: The target material in step S1 is a high-purity commercial graphite target. When doping the metal, the metal sheet is cut into pieces of 10 to 50 mm. 2 2 to 10 pieces of patches are attached in pairs to the symmetrical sputtering ring position of the target. The thickness of the metal sheet should be uniform and can be flexibly adjusted according to the needs of sputtering time. The metal can be selected from one or more of Au, Ag, Cu, Al, Mg, Zn, Ti, In, etc.
4. The method for preparing the interface modification layer material of the all-solid-state metal lithium battery according to claim 1, characterized in that: The substrate temperature is 15-200°C.
5. The method for preparing the interface modification layer material of the all-solid-state metal lithium battery according to claim 1, characterized in that: The coating chamber is evacuated to a pressure of ≤1×10 -4 Pa, the working gas is pure nitrogen, pure argon or a mixture of nitrogen and argon.
6. The method for preparing the interface modification layer material of the all-solid-state metal lithium battery according to claim 1, characterized in that: When the working gas is nitrogen, the nitrogen flow rate is 5 to 100 sccm; when the working gas is argon, the argon flow rate is 5 to 100 sccm; when the working gas is a mixture of nitrogen and argon, the nitrogen flow rate is 5 to 100 sccm and the argon flow rate is 0 to 100 sccm.
7. The method for preparing the interface modification layer material of the all-solid-state metal lithium battery according to claim 1, characterized in that: The RF sputtering power is 40 to 200 W, and the sputtering time is 60 s to 5 h.
8. The all-solid-state metal lithium battery interface modification layer material according to claim 1, characterized in that: Located between the solid electrolyte and the metallic lithium negative electrode, the homomorphic electrolyte type includes one or more of an amorphous electrolyte (LiPON, etc.), a perovskite type, a NASICON type, a garnet type, a halide type, a sulfide type, and a polymer / inorganic composite electrolyte type, and the selected positive electrode material may include all fully homomorphic battery positive electrode materials.